2004
DOI: 10.1523/jneurosci.4529-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Control of Cortical Neuron Migration and Layering: Cell and Non Cell-Autonomous Effects of p35

Abstract: The migration, arrest, and ultimately positioning of cortical neurons require signaling activity from Reelin as well as from cyclindependent kinase 5 (Cdk5). Although both molecules control neuronal positioning, they achieve their effects by quite separate molecular pathways. Cdk5 is a serine-threonine kinase, the activity of which is dependent on its activating subunits p35 and p39. Mice deficient in Cdk5, p35, or both p35 and p39 display the hallmarks of disturbed cortical development, including cortical lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…Clearly, late-born interneuron positioning in p35 mutants is unaffected despite the inversion of all pyramidal neuron layers. This confirms previous observations in p35 chimeras wherein all interneurons appear to be randomly distributed despite genotype-specific segregation of pyramidal neurons (Hammond et al, 2004). Similar conclusions, that interneuron positioning is unaffected by the Cdk5/p35 pathway, has been suggested previously in chimeric studies using Cdk5 mutants (Gilmore and Herrup, 2001).…”
Section: Discussionsupporting
confidence: 91%
“…Clearly, late-born interneuron positioning in p35 mutants is unaffected despite the inversion of all pyramidal neuron layers. This confirms previous observations in p35 chimeras wherein all interneurons appear to be randomly distributed despite genotype-specific segregation of pyramidal neurons (Hammond et al, 2004). Similar conclusions, that interneuron positioning is unaffected by the Cdk5/p35 pathway, has been suggested previously in chimeric studies using Cdk5 mutants (Gilmore and Herrup, 2001).…”
Section: Discussionsupporting
confidence: 91%
“…The interactions between these proteins and microtubules are largely regulated by posttranslational modification. In particular, the function of Dcx and kinesins appears to be regulated by phosphorylation by the Cdk5 kinase (Hammond et al, 2004; Nishimura et al, 2014). …”
Section: Neuronal Migrationmentioning
confidence: 99%
“…It has been shown that cortical interneurons, like pyramidal neurons (Angevine II and Sidman, 1961), are largely generated in an inside-out layering pattern within the neocortex (Fairen et al, 1986; Hammond et al, 2004; Miller, 1985; Rymar and Sadikot, 2007; Yozu et al, 2004). We have previously shown that this is also the case for MGE-derived interneurons (Miyoshi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%